Multimodal analgesia as a component treatment of complications in a child after penetrating orbital injury - Semkovych, Yaroslav; Semkovych, M; Меlnyk Taras; Gavrylyshyn, N (Pain medicine, 2022)
Introduction. Every year, about 2,000 children turn to ophthalmologists with eye damage of varying degrees of severity. The main causes of eye damage in children: active games with sticks, accidental contusions, injuries with sharp objects, unfortunate falls, fights, burns with chemical substances. Penetrating injuries occupy a special place a mong other eye injuries for two reasons. First of all, in the case of penetrating injuries, very delicate inner membranes and structures of the eye maybe damaged, which leads to serious complications. These cond point is the dangerof such formidable complications of the wound process as end ophthalmitis, sympathetic inflammation, etc. Background. We present a case of treatment of a penetrating wound of the orbitin a child who was treated in the Department of Anesthesiology and Intensive Care, CNE “Ivano-Frankivsk Regional Children’s Clinical Hospital of Ivano-Frankivsk Regional Council”. Results. A 9-year-old child was admitted to the ophthalmology department for treatment with complaints of pronounceds well in gand hyperemia of the eye lids, exophthalmos on the right, massive purulent discharge from the right eye, reduced movements of the right eye ball, hyperthermia. On the same day, she was operated on for phlegmon of the right orbit against the background of a penetrating wound of the right orbit of unknown etiology. Detoxification, multimodal, antibacterial, antiaggregant, immunoreplacement therapy was started. On the 10th day, the child was transferred to the ophthalmology department for further treatment, from where the child was discharged homein a satisfactory condition on the 27th day of the hospital stay. Conclusions. The child's recovery was achieved thanks to timely hospitalization, targeted antibacterial therapy, the use of multimodal anesthesia, immunoreplacement therapy, the use of nonspecific detoxification methods, and adequate rehydration therapy.